1999
DOI: 10.1177/096120339900800514
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in vascular smooth muscle cell proliferation: implications for prevention of arteriosclerosis

Abstract: Premenopausal women have a significant reduction in coronary artery disease compared to age-matched males. Little is known about the mechanism underlying this cardioprotective effect of estrogen. Contradictory evidence has been published and our lack of basic understanding of hormone interactions and bioavailability of different estrogens prevents definitive interpretation of these data. We demonstrate gender-specific effects in the proliferation of coronary artery vascular smooth muscle cells obtained from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…24, 26 Estrogen deficiency is thought to promote cardiovascular disease by promoting structural and functional changes in the blood vessels and via effects on multiple elements of the coagulation pathway. 2730 It is plausible that estrogen deficiency among post-menopausal women could potentiate the pathological mechanisms behind the increased risk of stroke related to anemia and higher hemoglobin concentrations (discussed above), potentially explaining why both low and high hemoglobin concentrations were strongly associated with increased risk of stroke in women but not men. Unfortunately, since more than 90% of women in this study fell in the post-menopausal age group, we did not have enough power to detect pre and post-menopausal differences in stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…24, 26 Estrogen deficiency is thought to promote cardiovascular disease by promoting structural and functional changes in the blood vessels and via effects on multiple elements of the coagulation pathway. 2730 It is plausible that estrogen deficiency among post-menopausal women could potentiate the pathological mechanisms behind the increased risk of stroke related to anemia and higher hemoglobin concentrations (discussed above), potentially explaining why both low and high hemoglobin concentrations were strongly associated with increased risk of stroke in women but not men. Unfortunately, since more than 90% of women in this study fell in the post-menopausal age group, we did not have enough power to detect pre and post-menopausal differences in stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this review, there seems to be an assumption that the sex of cells in culture is not important or is a detail that does not warrant reporting. This assumption is false, given the evidence that sex influences expression of genes in some cultured cells, tissues, organs and diseases, including cardiovascular disease [7,8,12,13,18-20]. In 2001, the General Accounting Office reported that pharmaceuticals withdrawn from the market in the USA had greater health risks for women than men (GAO-01-286R).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, femoralto-ankle pulse wave velocity, which provides an approximation of the stiffness of the lower extremity vasculature, was marginally lower in older HT women compared to older non-HT women (O non-HT: 1117 ± 28 cm/s; O HT: 1026 ± 36 cm/s; p = 0.06) and was significantly related to both popliteal lumen diameter and IMT in the entire study sample (Figure 4). Other beneficial actions of HT may include a reduction of vascular inflammatory factors such as cell adhesion molecules and matrix metalloproteinases, as well as inhibition of vascular endothelial growth factor, proliferation and/or migration of vascular smooth muscle cells [35][36][37].…”
Section: Discussionmentioning
confidence: 99%